Exploration on the impact of online supported methods for novice programmers - Sim, Tze Ying * (2015)
Programming is a challenging subject to students who are exploring it for the very first time. Common problems faced by the students are difficult to break down the main problem to sub-problems, providing a solution to the problem using specific steps and placing the different steps in the correct order to solve the problem. Three online supported methods are implemented in a programming 1 class across three semesters. They are online group discussion using Facebook group, the hour of code activities provided by code.org, and online journaling using Google Form. The impact of the three different are being discussed. It is observed that all the three methods increased students engagement towards the subject. Students posed questions, gave feedback and participated actively in the class. More study is needed to determine the impact of these methods toward students grade.